Relationship between seed yield and edaphic environment in subterranean clover - Carroni A.M.; Piano E.; Pecetti L. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Seed yield is a must for annual self-reseeding legumes to ensure reliable pasture regeneration from year to year. In subterranean clover, production of seed is expected to be influenced by the edaphic conditions, also in consideration of the particular morphophysiology of seed set. In this study, the effect of the edaphic environment on seed yield and the possible interaction between soil and genotype were assessed by growing a range of genotypes in two soil environments of distinct physical features, i.e., a clay loam and a coarse sandy loam soil. Genotype x soil environment interaction proved significant. Genotype response included either situations of contrasting behaviour in the two soil conditions or situations of stable performance, the latter suggesting a possible selection for wide adaptation. No relationship was found between genotype response and soil type at sites of origin.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)